Sistem Informasi Klinis Gangguan Pola Makan Pra Remaja Berbasis Web - Ahmad Ridhollohul Hakim (Melek IT : Information Technology Journal, 2019)
Dietary intake consumed pre teens currently do not regularly causing eating disorders. An eating disorder is a mental illness that can make a serious threat to a person's daily diet pattern, as eating in a number of very little or excessive eating. Discontent against the body more experienced by adolescent women than on men. That is because at startup as a teenager, a woman will tend to experience increased weakbody that makes her body becoming overweight or obese, while more men want her body experienced increased muscle era. This research aims to know the factors that affecting the dietary disorders at pre teens. This research method using prototype a method means in the development systemthat uses an approach to make a program quickly so it can be phased in & evaluation by the wearer. Engineering data collection done by filling questionnaire. Therefore this research make clinical information system disorder diet pre teens web based.